The Role of Perceived Variability and the Health Halo Effect in Nutritional Inference and Consumption. Issue 5 (May 2015) - Sundar, Aparna; Kardes, Frank R.
ABSTRACT: When information is missing or unknown, consumers often form nutritional inferences based on perceived attribute variability across brands. Four experiments show that less favorable nutritional inferences are formed when perceived attribute variability is high as opposed to low. This effect occurs when two attributes differing in perceived variability are presented or when the attribute is held constant and perceived variability is manipulated through priming. However, this effect is reduced when a health halo label is present as opposed to absent. Furthermore, the presence of a health halo label increases the amount of a product that is actually consumed when perceived attribute variability is high (vs. low) and when consumers learn from experience. Together, the results suggest that perceived attribute variability and the health halo effect jointly influence inference and behavior.